ON THE RESTRUCTURING OF DRAINAGE NETWORK OF THE BASE OF MOUNT ELBRUS - M. D. DOKUKIN; E. A. SAVERNYUK; A. M. BAGOV; A. V. MARKINA (Лëд и снег, 2015)
From 1957 to 2010, glaciers at the northeast foothills of Elbrus have significantly decreased in size. The area of the glaciers Birdzhalychiran and Chungurchatchiran have shrunk by 5.7 square kilometers. The shrinking in glacier thickness and the reduction in flow of glacier waters have resulted in the formation of barriers that look like riegels; at the same time, barriers that formed by dead ice of the medial moraine disappeared. This situation induced the constant change of glacial flow direction and the breach of lakes. The prediction for this area gives forthcoming radical reforming of the water network because of disappearance of the medial moraine ridge and the joining of the right-hand side of the river Birdzhaly-Su to the merging point of the river Kara-Kaya-Su.